2015
DOI: 10.1098/rsob.150014
|View full text |Cite
|
Sign up to set email alerts
|

A novel method for the purification of inositol phosphates from biological samples reveals that no phytate is present in human plasma or urine

Abstract: Inositol phosphates are a large and diverse family of signalling molecules. While genetic studies have discovered important functions for them, the biochemistry behind these roles is often not fully characterized. A key obstacle in inositol phosphate research in mammalian cells has been the lack of straightforward techniques for their purification and analysis. Here we describe the ability of titanium dioxide (TiO2) beads to bind inositol phosphates. This discovery allowed the development of a new purification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
144
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 121 publications
(150 citation statements)
references
References 47 publications
0
144
1
Order By: Relevance
“…However, a recent analysis of an HCT116 human colonic carcinoma cell line revealed it to contain substantially higher levels of InsP 8 than those found in some other mammalian cell lines [19]. We now demonstrate that there is considerable variability in the cellular levels of InsP 8 within two divergent HCT116 cell lines in our two laboratories.…”
Section: Introductionmentioning
confidence: 48%
See 2 more Smart Citations
“…However, a recent analysis of an HCT116 human colonic carcinoma cell line revealed it to contain substantially higher levels of InsP 8 than those found in some other mammalian cell lines [19]. We now demonstrate that there is considerable variability in the cellular levels of InsP 8 within two divergent HCT116 cell lines in our two laboratories.…”
Section: Introductionmentioning
confidence: 48%
“…This method does not match the sensitivity of HPLC, but by using TiO 2 beads to concentrate PP-InsPs prior to analysis [19], the cellular levels of total InsP 7 can be readily monitored. This methodology can even resolve 5-InsP 7 from 1-InsP 7 [20], but to date gel electrophoresis has not detected 1-InsP 7 in any mammalian cell line [19], perhaps because its levels are below the limits of sensitivity. Thus, we have developed an alternative HPLC technique that, for the first time, can directly measure 1-InsP 7 levels in intact cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PolyP extraction not only purifies polyP and RNA but also inositol phosphates (Fig. 2D), nucleotides (28), and likely free phosphate. The abundance of these phosphate-containing molecules influences these polyP quantification methods (8).…”
Section: Ppk1 the Only Enzyme Responsible For Polyp Synthesis Controlmentioning
confidence: 99%
“…In the future, we hope to improve the detection of PP-IPs directly from patient cells and tissue samples. It will be possible for us to apply and further develop the techniques of Saiardi et al who showed that PP-IPs are efficiently enriched on titanium oxide beads and can be visualized using the fluorescent dye 4 ′ ,6-diamidino-2-phenylindole (DAPI) (Wilson et al 2015).…”
Section: Resultsmentioning
confidence: 99%